2022
DOI: 10.2174/1386207324666210309100923
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Prognostic Signatures of Hepatocellular Carcinoma and the Potential Implications in Tumor Immune Microenvironment

Abstract: Objective: The objective of this study is to construct a prognostic model using genetic markers of liver cancer and explore the signature genes associated with the tumor immune microenviroment. Methods: Cox proportional hazards regression analysis was carried out to screen the significant HR using dataset of TCGA Liver Cancer (LIHC) gene expression data, then LASSO (Least absolute shrinkage and selection operator) was performed to select the minimal variables with significant HR of genes. Thus, the prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…DHX37 is an RNA helicase, which is significantly upregulated in 17 kinds of tumors ( Huang et al, 2021 ). DHX37 could affect the prognosis of patients with HCC or lung adenocarcinoma by immune infiltration, and can be used as a prognostic biomarker for HCC and lung adenocarcinoma ( Xu et al, 2020 ; Chen et al, 2022 ). Moreover, DHX37 acts as a function regulator of CD8 T cells ( Dong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…DHX37 is an RNA helicase, which is significantly upregulated in 17 kinds of tumors ( Huang et al, 2021 ). DHX37 could affect the prognosis of patients with HCC or lung adenocarcinoma by immune infiltration, and can be used as a prognostic biomarker for HCC and lung adenocarcinoma ( Xu et al, 2020 ; Chen et al, 2022 ). Moreover, DHX37 acts as a function regulator of CD8 T cells ( Dong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent bioinformatic analysis of DHX37 expression profiles in multiple have cancers also shown that DHX37 is a potential marker and is associated with the tumor immune microenvironment in liver cancer (9)(10)(11). However, the molecular mechanisms underlying the pro-oncogenic role of DHX37 in liver cancer remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…DHX37 can inhibit the activation of antigen-specific CD8-positive T cells, thus antagonizing the efficacy of immunotherapy for triple-negative breast cancer ( 8 ). Recent bioinformatic analysis of DHX37 expression profiles in multiple have cancers also shown that DHX37 is a potential marker and is associated with the tumor immune microenvironment in liver cancer ( 9–11 ). However, the molecular mechanisms underlying the pro-oncogenic role of DHX37 in liver cancer remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%